Rationale for In-Neonatal Intensive Care Unit Administration of Live, Attenuated Rotavirus Vaccination - Briggs-Steinberg, Courtney; Shah, Shetal (American Journal of Perinatology, 2018)
Rotavirus is the most common nonseasonal vaccine preventable illness. Despite increased severity of rotaviral illness in early infancy, most neonatal intensive care units (NICU) do not administer rotavirus vaccination either during the NICU stay at age of eligibility or at discharge as the Advisory Committee on Immunization Practices recommends. In this commentary, we review the rationale for the administration of rotavirus vaccination to premature infants. Further, we outline data supporting vaccine administration at chronologic age while still admitted to the NICU.
Keywords: rotavirus; immunization; NICU; premature infants